1987
DOI: 10.1152/ajpgi.1987.252.4.g535
|View full text |Cite
|
Sign up to set email alerts
|

Processing of receptor-bound somatostatin: internalization and degradation by pancreatic acini

Abstract: We have previously demonstrated the presence of specific binding sites for somatostatin on plasma membranes from pancreatic acinar cells. In the present study we attempted to characterize the fate of receptor-bound 125I-[Tyr11]somatostatin. Internalization of somatostatin was rapid (reaching a plateau at 20% of the cell-associated specific radioactivity) and temperature dependent. To follow the processing of bound somatostatin, acini were incubated with 125I-[Tyr11]somatostatin at 5 degrees C during 16 h then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…It is tempting to speculate that the abrupt decrease in the concentration of somatostatin binding sites observed in the N. parabrachialis lateralis and the N. locus coeruleus during the perinatal period may be ascribed to neural and/or endocrine regulation of receptor gene expression. It has previously been shown that somatostatin inhibits the expression of its own receptors in anterior pituitary cells (Draznin et al, 1985;Mentlein et al, 1989), pancreatic acinar cells (Viguerie et al, 1987), and anterior pituitary tumor cells (Reisine and Axelrod, 1983;Heisler and Srikant, 1985). Therefore, the decrease in the density of somatostatin binding sites observed in the human brainstem nuclei during development might also result from downregulation of the receptors by endogenous somatostatin.…”
Section: Developmental Changes In the Density Of Somatostatin Bindingmentioning
confidence: 96%
“…It is tempting to speculate that the abrupt decrease in the concentration of somatostatin binding sites observed in the N. parabrachialis lateralis and the N. locus coeruleus during the perinatal period may be ascribed to neural and/or endocrine regulation of receptor gene expression. It has previously been shown that somatostatin inhibits the expression of its own receptors in anterior pituitary cells (Draznin et al, 1985;Mentlein et al, 1989), pancreatic acinar cells (Viguerie et al, 1987), and anterior pituitary tumor cells (Reisine and Axelrod, 1983;Heisler and Srikant, 1985). Therefore, the decrease in the density of somatostatin binding sites observed in the human brainstem nuclei during development might also result from downregulation of the receptors by endogenous somatostatin.…”
Section: Developmental Changes In the Density Of Somatostatin Bindingmentioning
confidence: 96%
“…Complete purification of the three Bodipy-labeled peptides was easily achieved as the observed elution times of each HPLC fractions were clearly different (35,44,58, and 63 min for native SRIF and its ␣-, ⑀ 4 -, and ⑀ 9 -Bodipy analogs, respectively). Complete purification of the three Bodipy-labeled peptides was easily achieved as the observed elution times of each HPLC fractions were clearly different (35,44,58, and 63 min for native SRIF and its ␣-, ⑀ 4 -, and ⑀ 9 -Bodipy analogs, respectively).…”
Section: Molecular Characterization Of Fluorescent [D-trp 8 ]Srif Dermentioning
confidence: 99%
“…Several reports indicate that SRIF is internalized in pancreatic (34,35), hypophyseal (36,37,38), and human carcinoid tumor (39) Several reports indicate that SRIF is internalized in pancreatic (34,35), hypophyseal (36,37,38), and human carcinoid tumor (39) …”
mentioning
confidence: 99%
“…Thus although receptor-mediated internalization of the ligand is not thought to participate in the down-regulation of membrane SRIF-binding sites on tumorous cell lines (Presky & Schonbrunn, 1986), it may be involved in their autoregulation in normal pituitary tissue. This possibility is supported by the demonstration that sig¬ nificant (15%) internalization of membrane-bound SRIF occurs in normal rat anterior pituitary cells (Draznin, Sherman, Sussman et al 1985) and pan¬ creatic tissue (Viguerie, Esteve, Susini et al 1987) within 15-20 min of incubation, whereas receptormediated internalization of SRIF in tumorous cells is not rapidly induced (Presky & Schonbrunn, 1986). The rapid down-regulation of SRIF-binding sites in the chicken pituitary gland may, therefore, be similar li 11 tí°c Hĉ e Q.…”
Section: Homologous Regulation Of Srif-binding Sitesmentioning
confidence: 93%